Experimental investigation of tensile properties and fracture behavior of ophthalmic sutures under straight, knotted, and looped configurations: Vicryl, nylon, and polypropylene - Rasmiranjan Dalai; Vinay S; Sai N.S.H.C; Vineet J; Ramji M; Sayan B; Viswanath C (PLoS ONE, 2026)
The deformation and failure behavior of sutures play a vital role in the surgical outcomes of soft tissue encountered in ophthalmic surgeries. In the present study, the mechanical characteristics of ophthalmic sutures, including 6–0/7–0/8–0 braided-Vicryl, 8–0/9–0/10–0 monofilament-Nylon, and 9–0/10–0 monofilament-Polypropylene sutures, are investigated under straight configuration (SC), knotted configuration (KC), and looped configuration (LC). Uniaxial tensile tests of sutures were conducted according to ASTM D2256/D2256M-21 at a strain rate of 30 mm/min with a gauge length of 120 mm. The initial stiffness, yield strength, breaking strength, elongation at break, resilience, and work of rupture were obtained from the experiments. Vicryl and Nylon sutures exhibited an S -shaped load vs. extension response, while Polypropylene exhibited an R -shaped profile. The sutures in SC displayed a smooth load vs. extension curve. Whereas the sutures in KC and LC showed a small load drop in the inelastic region during the full development of the knot. Further, fractography of failed surfaces was investigated using SEM to characterize the fracture behavior. Vicryl sutures predominantly failed in the high-strain-rate tensile break, whereas Nylon and Polypropylene sutures failed in the low-strain-rate tensile break in the SC. Meanwhile, the sutures in KC and LC experienced mainly tensile-shear failure due to the presence of knots. The present study’s outcomes help surgeons select an appropriate suture for a given ophthalmic tissue, thereby achieving a better surgical outcome based on its mechanical properties.